2008
DOI: 10.1208/s12249-008-9109-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Four-fluid Nozzle Spray Drier to Prepare Inhalable Rifampicin-containing Mannitol Microparticles

Abstract: Abstract. The purpose of this study was to use a four-fluid nozzle spray drier as a new one-step method for preparing rifampicin (RFP)-containing mannitol microparticles. A RFP-acetone/methanol (2:1) solution and aqueous solutions of mannitol (MAN) were simultaneously supplied through different liquid passages of a four-fluid nozzle spray drier and then dried to obtain MAN microparticles containing RFP. Using a cascade impactor, the in vitro aerosol performance of RFP powder and RFP-MAN microparticles with 1:5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…29,[40][41][42][43] However, many different techniques can be used to achieve this goal, such as using the nanoparticles, 44 using the micronized form of poorly water-soluble drugs 45,46 and even using four-fluid spray driers to prepare microparticles containing water-insoluble drugs. [47][48][49] In this study, the theophylline agglomerate was prepared at a respirable particle size (1-5 µm) using the solvent antisolvent technique. 29,[45][46][47][48][49][50] First, the drug was dissolved with stearic acid in an organic solvent and then precipitated as nanoparticles by dropping this solution into an antisolvent.…”
Section: Resultsmentioning
confidence: 99%
“…29,[40][41][42][43] However, many different techniques can be used to achieve this goal, such as using the nanoparticles, 44 using the micronized form of poorly water-soluble drugs 45,46 and even using four-fluid spray driers to prepare microparticles containing water-insoluble drugs. [47][48][49] In this study, the theophylline agglomerate was prepared at a respirable particle size (1-5 µm) using the solvent antisolvent technique. 29,[45][46][47][48][49][50] First, the drug was dissolved with stearic acid in an organic solvent and then precipitated as nanoparticles by dropping this solution into an antisolvent.…”
Section: Resultsmentioning
confidence: 99%
“…The aerosolisation pattern of rifampicin was improved when microencapsulated with mannitol. However, intratracheal of the drug remained in the lung after 1 h) (Mizoe et al, 2008), indicating an efficacy below the desired level to attain a therapeutic effect. This result was rather predictable, as mannitol is very soluble in aqueous medium and even in the presence of a small quantity of medium, as that existing in the alveolar zone, rapid dissolution of the microparticle matrix is expected, releasing the drug and enabling its rapid elimination.…”
Section: Polyalcohol Microparticlesmentioning
confidence: 99%
“…Lung drug concentration was 10-times higher after direct lung delivery (Hwang et al, 2008) Mannitol Rifampicin Intratracheal Microparticles Drug elimination is very rapid, with only 4% of drug remaining in the lung 1h after administration (Mizoe et al, 2008) Alginate Chitosan…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…38 Mizoe et al 39 successfully prepared respirable rifampin (RFP)-mannitol (MAN) microparticles using a four-fluidnozzle spray drier. They found that RFP-MAN microparticles were effective in pro-releasing RFP in the lungs.…”
Section: Inhalable Rifampin-containing Mannitol Microparticlesmentioning
confidence: 99%
“…However, further research on such DDSs that target alveolar macrophages for the sustained release of RFP and other drugs is required. 39 …”
Section: Inhalable Rifampin-containing Mannitol Microparticlesmentioning
confidence: 99%